Analysis of financial management behavior level of generation Y in Padang City - Rahmedia Nasli; Yolandafitri Zulfia (Universitas Negeri Padang, 2021)
This study aims to determine how the level of financial management behavior in Generation Y in The city of Padang. Type of quantitative research with descriptive method. The sample in this study Generation Y in the city of Padang amounted to 240 people. The technique used in this research is cluster random sampling. The results of this study indicate that the level of financial management behavior in Generation Y in Padang City is in the sufficient category with a score of 3,83 (77%); consumption with a score of 3,84 (77%); cash-flow management with a score 3,68 (74%); saving and investment with a score 3,95 (79%).